(untitled) (Journal of EAHIL, 2015)
Over the past decade, “Boot Camps” have become popular among research librarians as an alternative to traditional professional development venues, such as conferences. Boot Camps provide an intense immersion on current topics of interest as well as an opportunity for onsite learning in the presence of faculty, researchers, students, and other library patrons.